2005
DOI: 10.24965/gapp.vi32.382
|View full text |Cite
|
Sign up to set email alerts
|

Regulación y calidad de los servicios públicos liberalizados

Abstract: Palabras clave: Servicios públicos, liberalización, calidad de los servicios públicos, evaluación. La calidad de los servicios públicos de red: ¿el coste oculto de la liberalización?1 Las industrias de servicios en general, incluyendo la banca y los servicios financieros, seguros, servicios profesionales, pensiones, sanidad y servicios públicos domiciliarios, han estado sometidas en los últimos años a un generalizado proceso de liberalización. Este proceso ha sido especialmente intenso en el caso de las indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The decline in the quality of service of electric distribution utilities in Latin America is a topic requiring investigation because of its effect on the sustainability of privatization (Millan, 2006;Nellis, 2004;Shirley, 2004). The quality of service could be a hidden cost of privatization because the policies of regulation have neglected the quality-of-service issue (Costas, 2006). A factor related to the regulatory regimes that provide economical incentives to the firms could explain the reduction in quality (Berg, 2006;Kidokoro, 2002;Sheshinski, 1976;Spence, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The decline in the quality of service of electric distribution utilities in Latin America is a topic requiring investigation because of its effect on the sustainability of privatization (Millan, 2006;Nellis, 2004;Shirley, 2004). The quality of service could be a hidden cost of privatization because the policies of regulation have neglected the quality-of-service issue (Costas, 2006). A factor related to the regulatory regimes that provide economical incentives to the firms could explain the reduction in quality (Berg, 2006;Kidokoro, 2002;Sheshinski, 1976;Spence, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…According to Macedo (2004), researchers could improve cost-efficiency studies by incorporating a measure of quality of service in the analysis because a trade-off between the quality of service and the reduction of costs exists. Moreover, researchers have identified that the level of quality of service in the electric industry is diminishing progressively, negatively affecting consumers' acceptance of the reform (Berg, 2006;Costas, 2006;Shirley, 2004). Therefore, a relevant issue requiring research involves understanding why electric distribution utilities are lowering the quality of service.…”
Section: Background Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations